PENGEMBANGAN BAHAN AJAR BERBASIS KASUS (CASE BASED) PADA MATA KULIAH ASPEK HUKUM EKONOMI DAN BISNIS - Sriyani Mentari; Nujmatul Laily (JURNAL PENDIDIKAN AKUNTANSI, 2014)
This research aims to develop case based learning materials for business and economic law course. The development usedÂ  Borg and Gall (1983) model that is modified into ten procedure. The main activities of this research are designing and developing learning materials, and 2) validating and revising learning materials. Learning materials is designed into 11 chapters which each chapters consists of: cases, aperseption, learning objective, material and exercises. Validation of learning materials is done by two validators that have competencies in the business law. Validation result of learning materials show that cases are relevan and original where it can motivate the student to have critical thinking. Learning material presentation based on the order from easy to difficult and can achieve the learning objective. Validation results conclude that learning materials are proper and valid and it can be tested in a larger stage. Â